2016
DOI: 10.1371/journal.pone.0165896
|View full text |Cite
|
Sign up to set email alerts
|

Telipogon peruvianus (Orchidaceae) Flowers Elicit Pre-Mating Behaviour in Eudejeania (Tachinidae) Males for Pollination

Abstract: Several neotropical orchid genera have been proposed as being sexually deceptive; however, this has been carefully tested in only a few cases. The genus Telipogon has long been assumed to be pollinated by male tachinid flies during pseudocopulatory events but no detailed confirmatory reports are available. Here, we have used an array of methods to elucidate the pollination mechanism in Telipogon peruvianus. The species presents flowers that have a mean floral longevity of 33 days and that are self-compatible, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Rewardless Andean orchids in the genera Trichoceros and Telipogon have long been suspected of sexual deception, using male tachinid flies as dupes (van der Pijl and Dodson 1966). Recent work by Martel et al (2016) demonstrated that the flowers of Telipogon peruvianus attract male Eudejeania tachinid flies as pollinators. Chemical and behavioral analyses revealed that these flowers mimic both the cuticular hydrocarbon blend used by female Eudejeania flies to attract males and the yellow ray florets of the aster flowers upon which male flies seek mates in montane habitats (Martel et al 2019).…”
Section: Obligate Mutualism and Brood-site Deception: The Reproductivmentioning
confidence: 99%
“…Rewardless Andean orchids in the genera Trichoceros and Telipogon have long been suspected of sexual deception, using male tachinid flies as dupes (van der Pijl and Dodson 1966). Recent work by Martel et al (2016) demonstrated that the flowers of Telipogon peruvianus attract male Eudejeania tachinid flies as pollinators. Chemical and behavioral analyses revealed that these flowers mimic both the cuticular hydrocarbon blend used by female Eudejeania flies to attract males and the yellow ray florets of the aster flowers upon which male flies seek mates in montane habitats (Martel et al 2019).…”
Section: Obligate Mutualism and Brood-site Deception: The Reproductivmentioning
confidence: 99%
“…Floral scents are not solely employed to attract male Euglossini bees. These fragrances are equally important on mechanisms based on deception, acting as a fake signal to mislead insects looking for food or sexual partners (Aguiar 2014;Martel et al 2016). In some cases, these compounds are unnoticeable to the human nose.…”
Section: Deceptive Strategiesmentioning
confidence: 99%
“…In principle, the form of the lip might act as a visual signal to mate-searching males and also ensure the correct alignment between the body of the pollinator and the reproductive parts of the plant (Kullenberg, 1961(Kullenberg, , 1973Phillips et al, 2014;De Jager & Peakall, 2015;G€ ogler et al, 2015;Martel et al, 2016). Selection on the lip form could be thus imposed through both the sensory preferences of the pollinator and the mechanical fit between the pollinator and the lip (De Jager & Peakall, 2015).…”
Section: Introductionmentioning
confidence: 99%